The Effect of Hypnobirthing on Anxiety Levels Related to the Duration of Labor at Klinik Pratama Sejahtera in 2025 - Rismeni Saragih (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Hypnobirthing is a relaxation technique and altered state of awareness that can help reduce anxiety during childbirth and potentially influence the duration of labor. This study aimed to determine the effect of hypnobirthing on anxiety levels related to the duration of labor among pregnant women at Klinik Pratama Sejahtera in 2025. This study employed a quasi-experimental research design. The population and sample consisted of 39 pregnant women who received maternity care at Klinik Pratama Sejahtera in 2025, selected using total sampling. The data used in this study were primary and secondary data collected through questionnaires. Data analysis was conducted using bivariate analysis with the Chi-square test. The results showed a significant effect of hypnobirthing on anxiety levels related to the duration of labor, with a significance value of p = 0.003 (< 0.05). Mothers who practiced hypnobirthing experienced lower anxiety levels compared to those who did not practice hypnobirthing. These findings indicate that hypnobirthing is effective in reducing maternal anxiety prior to and during labor. In conclusion, hypnobirthing has a significant effect on reducing anxiety levels related to the duration of labor. Therefore, pregnant women are encouraged to actively practice hypnobirthing or perform regular and independent relaxation techniques as an effort to reduce anxiety and prevent prolonged labor.